Metabolic Alterations in a Slow-Paced Model of Pancreatic Cancer-Induced Wasting. (26th February 2018) - Wyart, Elisabeth; Reano, Simone; Hsu, Myriam Y.; Longo, Dario Livio; Li, Mingchuan; Hirsch, Emilio; Filigheddu, Nicoletta; Ghigo, Alessandra; Riganti, Chiara; Porporato, Paolo Ettore
Abstract : Cancer cachexia is a devastating syndrome occurring in the majority of terminally ill cancer patients. Notably, skeletal muscle atrophy is a consistent feature affecting the quality of life and prognosis. To date, limited therapeutic options are available, and research in the field is hampered by the lack of satisfactory models to study the complexity of wasting in cachexia-inducing tumors, such as pancreatic cancer. Moreover, currently used in vivo models are characterized by an explosive cachexia with a lethal wasting within few days, while pancreatic cancer patients might experience alterations long before the onset of overt wasting. In this work, we established and characterized a slow-paced model of pancreatic cancer-induced muscle wasting that promotes efficient muscular wasting in vitro and in vivo . Treatment with conditioned media from pancreatic cancer cells led to the induction of atrophy in vitro, while tumor-bearing mice presented a clear reduction in muscle mass and functionality. Intriguingly, several metabolic alterations in tumor-bearing mice were identified, paving the way for therapeutic interventions with drugs targeting metabolism.